Effects of hypotonic stress and ouabain on the apparent diffusion coefficient of water at cellular and tissue levels in Aplysia. (8th January 2014) - Jelescu, Ileana Ozana; Ciobanu, Luisa; Geffroy, Françoise; Marquet, Pierre; Le Bihan, Denis
<x xml:space="preserve">Abstract</x> There is evidence that physiological or pathological cell swelling is associated with a decrease of the apparent diffusion coefficient (ADC) of water in tissues, as measured with MRI. However the mechanism remains unclear. Magnetic resonance microscopy, performed on small tissue samples, has the potential to distinguish effects occurring at cellular and tissue levels. A three‐dimensional diffusion prepared fast imaging with steady‐state free precession sequence for MR microscopy was implemented on a 17.2 T imaging system and used to investigate the effect of two biological challenges known to cause cell swelling, exposure to a hypotonic solution or to ouabain, on Aplysia nervous tissue. The ADC was measured inside isolated neuronal soma and in the region of cell bodies of the buccal ganglia. Both challenges resulted in an ADC increase inside isolated neuronal soma (+31 ± 24% and +30 ± 11%, respectively) and an ADC decrease at tissue level in the buccal ganglia (−12 ± 5% and −18 ± 8%, respectively). A scenario involving a layer of water molecules bound to the inflating cell membrane surface is proposed to reconcile this apparent discrepancy. Copyright © 2014 John Wiley & Sons, Ltd.